Effect of maternal hyperalimentation on intrauterine growth retardation. - De Prins, F (1988)
The effect of maternal hyperalimentation on intrauterine growth retardation was studied by performing unilateral uterine vessel ligation on day 17 in Wistar rats. Test animals were given food supplements by gavage for three days postoperatively whereas control animals received saline. The caloric intake and weight gain of the test dams was significantly greater than that of the controls from days 17 to 20 but not over the longer period, day 14 to 23. The survival and growth of fetuses in the unoperated horn were similar in test and control rats. Fetal survival in the ligated horn was doubled by maternal food supplementation but the growth and development of the survivors were not improved.